"[Existing] While Black": Race, Gender, and the Surveillance of Blackness. Issue 2 (4th March 2022) - Okello, Wilson Kwamogi
Abstract: This manuscript carefully examines racialized surveillance, a mechanism of anti-Black violence, or what Hartman has called the afterlife of slavery, that persists in society despite the formal end of enslavement. To accomplish this, I conducted a critical discourse analysis of an incident in the public sphere and one in an educational context to show the ways anti-Black sentiments flow between them in similar ways. Specifically, this analysis examined the controversial Starbucks incident that involved a White manager calling the police on two Black men, and the experience of Lolade Siyonbola, who was napping in a commons at Yale University. Responding to the pressing question, how do we exist, in the bodies that we hold, in this historical moment and into the future, methodologically, I think with histories of Black men and Black women in the white imaginary and Foucault's instruments of power to interrogate anti-Black logics affecting Black people in public and educational contexts.